PEMBERIAN PAKAN BERBEDA PADA BENIH IKAN SIDAT (Anguilla sp.) YANG BERASAL DARI KUALA BUBON SEBAGAI UPAYA DOMESTIKASI - Sufal Diansyah; Neneng Marlian (Universitas Teuku Umar, 2016)
Eel (Anguilla sp) is an export commodity from fisheries and high economic value . Indonesia has high potency of eel elver and glass ell, but until now its use for aquaculture is still very low. The aims of this study were to fishculture system with enviromental approach and management of feeding the eel growth in container cultivation as domestication. This study was conducted from March to May 2016. The experimental design used was a completely randomized design with three different feeding treatments and each treatment was repeated three times. The eel was used for this studied Anguilla sp. of stadia elver with an average weight 0,5 gram/fish. The results showed that different feeding treatment giving significantly affect all parameters. The best feeding was mixture of feed pellets and tubifex with a survival of 73.92 %, growth rate of 0.030 g, the biomass growth rate of 9.07 g/day, and the feed conversion of 1.32.